Analysis and application of electrostatic discharge testing standards for device level charged device models - Jiang Hui; Tang Zhen; Wang Qianqian; Wan Yongkang; Yu Yongjian (Dianzi Jishu Yingyong, 2025)
This article summarizes, analyzes, and interprets the main testing standards for electrostatic discharge of device level charged device models (CDM) both domestically and internationally. The differences and correlations between various standards were sorted out, and the application scope and technical points of each standard were clarified. The impact factors and control methods that affect the testing results of device level charged device models (CDM) were deeply studied. Relevant technical skills were proposed to ensure the consistency and accuracy of test results in the standard application process, providing guidance for the selection, testing, and engineering application of device level charged device model testing standards.